Current Status of Endoscopic Ultrasound Techniques for Pancreatic Neoplasms - Nakai, Yousuke (Clin Endosc, 2019)
Endoscopic ultrasound (EUS) now plays an important role in the management of pancreatic neoplasms. There are various types of pancreatic neoplasms, from benign to malignant lesions, and the role of EUS ranges from the imaging diagnosis to treatment. EUS is useful for the detection, characterization, and tissue acquisition of pancreatic lesions. Recent advancement of contrast-enhanced harmonic EUS and elastography enables better characterization of pancreatic lesions. In addition to these enhanced EUS imaging techniques, EUS-guided tissue acquisition is now the standard procedure to establish the pathological diagnosis of pancreatic neoplasms. While these diagnostic roles of EUS have been established, EUS-guided interventions such as ablation and drainage are also increasingly utilized in the management of pancreatic neoplasms. However, most of these EUS-guided interventions are not yet standardized in terms of techniques and devices and thus need further investigations.